2019
DOI: 10.1002/qj.3500
|View full text |Cite
|
Sign up to set email alerts
|

Convective activity in an extratropical cyclone and its warm conveyor belt – a case‐study combining observations and a convection‐permitting model simulation

Abstract: Warm conveyor belts (WCBs) are important Lagrangian features in extratropical cyclones for the evolution of clouds, precipitation and flow dynamics. According to the classical concept, WCBs rise continuously from the boundary layer to the upper troposphere with ascent rates of less than 50 hPa/hr. Recent studies identified embedded convection in WCBs with ascent rates exceeding 50 hPa/hr, however, its significance and characteristics have not yet been analysed systematically. This study presents a detailed ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
179
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(227 citation statements)
references
References 76 publications
32
179
2
Order By: Relevance
“…WCB ascent has been shown to include sporadic periods of intense, convective‐like ascent (e.g. Browning, ; Oertel et al ., ) and may explain the strongest dependence of the WCB to the convection and cloud parametrizations found here. For this case‐study we have demonstrated that modifying parametrized diabatic processes changed the properties of the WCB, the diabatic heating of air parcels in the WCB ascent, and the upper‐level ridge amplification and block forecast.…”
Section: Discussionmentioning
confidence: 55%
“…WCB ascent has been shown to include sporadic periods of intense, convective‐like ascent (e.g. Browning, ; Oertel et al ., ) and may explain the strongest dependence of the WCB to the convection and cloud parametrizations found here. For this case‐study we have demonstrated that modifying parametrized diabatic processes changed the properties of the WCB, the diabatic heating of air parcels in the WCB ascent, and the upper‐level ridge amplification and block forecast.…”
Section: Discussionmentioning
confidence: 55%
“…Another ridge exists around 20 • W-10 • E (label R3), which is characterized by ridge building between 2 and 3 days (Figure 2a,b). This ridge building was associated with the development of cyclone Vladiana (labelled V in Figure 2), which was another observational highlight during the NAWDEX period, due to the occurrence of pronounced warm-conveyor-belt ascent (Schäfler et al, 2018;Oertel et al, 2019). In the following, ridge R3 is characterized by a large amplitude and a similar nonlinear evolution to ridge R1, albeit its spatial extent is smaller than that of ridge R1 (Figure 2c,d).…”
Section: Synoptic Overview and Variance Evolutionmentioning
confidence: 86%
“…; Oertel et al . ). In the following, ridge R3 is characterized by a large amplitude and a similar nonlinear evolution to ridge R1, albeit its spatial extent is smaller than that of ridge R1 (Figure c,d).…”
Section: Quantitative View Of the Variance Amplificationmentioning
confidence: 99%
“…Diabatic processes are particularly important in warm conveyor belts (WCBs), which are coherent, typically poleward-ascending airstreams associated with extratropical cyclones (Harrold, 1973;Browning, 1986Browning, , 1999Wernli and Davies, 1997). During their typically slantwise cross-isentropic ascent from the boundary layer ahead of the cold front to the upper troposphere, they form large-scale, mostly stratiform cloud bands and play a key role in the distribution of surface precipitation (e.g., Browning, 1986;Eckhardt et al, 2004;Madonna et al, 2014;Pfahl et al, 2014;Flaounas et al, 2018).…”
mentioning
confidence: 99%
“…Although WCBs are typically described as gradually ascending and mainly stratiform-cloud-producing airstreams (e.g., Browning, 1986;Madonna et al, 2014), the concept of rapid convective motion embedded in the frontal cloud band of the WCB had already been proposed in 1993 (Neiman et al, 1993). Recent studies have suggested that the WCB is, at least in some cases, not a homogeneously ascending airstream: in contrast, the detailed ascent behavior of the individual WCB trajectories associated with one extratropical cyclone can vary substantially (e.g., Rasp et al, 2016;Oertel et al, 2019), and convective activity can be frequently embedded in the largescale baroclinic region of the WCB. This has been identified, e.g., with various remote-sensing data (Binder, 2016;Crespo and Posselt, 2016;Flaounas et al, 2016Flaounas et al, , 2018, with online trajectories in convection-permitting simulations (Rasp et al, 2016;Oertel et al, 2019), and in coarser simulations with parameterized convection (Agustì-Panareda et al, 2005;.…”
mentioning
confidence: 99%